Compartmentalization of Intrarenal Programmed Cell Death Protein 1-Ligand 1 and Its Receptor in Kidney Injury Related to Immune Checkpoint Inhibitor Nephrotoxicity - Tampe, Désirée; Kopp, Sarah Birgit; Baier, Eva; Hakroush, Samy; Tampe, Björn (Frontiers in Medicine, 2022)
Background: Due to advantages in cancer therapy, immune checkpoint inhibitors (ICIs) are new classes of drugs targeting programmed cell death protein 1-ligand 1 (PD-L1) or its receptor (PD-1) used in many cancer therapies. Acute interstitial nephritis (AIN) is a potential and deleterious immune-related adverse events (irAE) and the most common biopsy-proven diagnosis in ICI-related nephrotoxicity. AIN in patients receiving ICIs is was only seen in cases with tubular PD-L1 positivity, while PD-1 expression is limited to inflammatory cells and also observed in injured kidneys independent of ICI therapy. We have previously described that PD-L1 positivity can also be detected in glomerular and endothelial compartments. We here aimed to describe compartmentalization of renal PD-L1 expression specifically in injured kidneys with confirmed nephrotoxicity related to ICIs, its association with presence of PD-1, and clinical findings. Methods: We included human kidney samples with AIN related to ICI therapy to describe PD-L1 and PD-1 expression localized to different renal compartments in association with clinical and laboratory parameters. Results: We herein report compartmentalization of PD-L1 with tubular positivity in all cases, partially overlapping with glomerular and endothelial PD-L1 positivity. Furthermore, we provide evidence that tubular PD-L1 in ICI-related nephrotoxicity correlates with levels of C-reactive protein (CRP), while glomerular and endothelial PD-L1 positivity with lower serum levels of complement component C4. Interestingly, glomerular PD-L1 correlated with kidney function, while interstitial cell PD-1 positivity specifically with severity of kidney injury. Finally, we provide evidence for signaling pathways associated with intrarenal PD-L1/PD-1 expression.